2006
DOI: 10.1093/chemse/bjj049
|View full text |Cite
|
Sign up to set email alerts
|

A Specific Heat Shock Protein Enhances the Expression of Mammalian Olfactory Receptor Proteins

Abstract: Multiple trials failed to express significant amounts of olfactory receptors in heterologous cells as they are typically retained in the endoplasmic reticulum (ER). Evidence is accumulating that cell-type-specific accessory proteins regulate the folding of olfactory receptors, their exit from the ER, and the trafficking to the plasma membrane of the olfactory cilia where the receptors gain access to odorants. We found Hsc70t, a testis-enriched variant of the Hsp70 family of heat shock proteins which is specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0
2

Year Published

2006
2006
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 56 publications
2
66
0
2
Order By: Relevance
“…OR2AG1-RLuc plasmid was obtained by subcloning the coding sequences of Renilla luciferase (RLuc) from the plasmid pGFP2-multiple cloning site-RLuc(h) (Packard BioScience, Meriden, CT) into the ClaIlinearized, odorant-receptor-containing plasmid. The OR2AG1-GFP and OR2AG1-RLuc fusion proteins were tested for functionality by Ca 2ϩ imaging using amylbutyrat (Neuhaus et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…OR2AG1-RLuc plasmid was obtained by subcloning the coding sequences of Renilla luciferase (RLuc) from the plasmid pGFP2-multiple cloning site-RLuc(h) (Packard BioScience, Meriden, CT) into the ClaIlinearized, odorant-receptor-containing plasmid. The OR2AG1-GFP and OR2AG1-RLuc fusion proteins were tested for functionality by Ca 2ϩ imaging using amylbutyrat (Neuhaus et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…To investigate whether ORs also undergo regulated internalization from the cell surface, trafficking of recombinant OR2AG1-GFP fusion protein was analyzed in heterologous cells by confocal microscopy. Treatment with its cognate ligand amylbutyrat (Neuhaus et al, 2006) resulted in redistribution of OR2AG1-GFP from the plasma membrane to intracellular vesicles ( Fig. 1 A, B).…”
Section: Activated Ors Are Internalized and Accumulate In Recycling Ementioning
confidence: 98%
“…Those cells that functionally expressed either OR7A5 or OR4D1 displayed robust Ca 2ϩ signals when exposed to the stimulus mixture (data not shown), whereas stimulus-dependent Ca 2ϩ responses were never observed in nontransfected cells. We then divided the stimulus into different submixtures (17,(55)(56)(57) and determined the specific fraction activating either OR7A5 or OR4D1, respectively. After several such cycles, we identified two receptor-ligand pairs.…”
Section: Distinct Agonist Profiles Of Three Human Testicularmentioning
confidence: 99%
“…Hsp70 proteins have been suggested to promote the processing of both wild-type and mutant GPCRs to the PM. For example, the testis enriched Hsp70 variant, Hsc70t/HspA1L, enhances the expression and trafficking to the cell surface of odorant receptors (Neuhaus et al 2006); whilst Hsc70 has been demonstrated to interact with cytoplasmic domains of non-glycosylated angiotensin II type 1 receptor (Lanctot et al 2006). Furthermore, in cultured cells, the Hsp70 cochaperone HSJ1b can modulate the processing of the archetypal GPCR rhodopsin.…”
Section: Molecular Chaperones As Regulators Of Protein Degradationmentioning
confidence: 99%